Imagination of Singapore : the de-construction of Singapore's identity using discourse of employment. - Lim, Wei-Peng. (2008)
In this study, we attempt to make uncover this impact via 179 articles about issues of employment. These articles appeared in the Straits Times between 1995 and 2003.